Rapid prototyping foam board and processing technology thereof

CN122898074APending Publication Date: 2026-10-13SHANGHAI ENJI THERMAL INSULATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611240833.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

现有聚苯乙烯泡沫板依然存在成型慢、阻燃性差、燃烧时烟雾释放量大的问题

Benefits of technology

本发明提供了一种快速成型的泡沫板及其加工工艺,本发明通过以下方法有效提高了聚苯乙烯泡沫板的成型速度、阻燃性,同时还大幅度降低了聚苯乙烯泡沫板燃烧时的烟雾释放量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of foam board of rapid prototyping and processing technology thereof, it is related to polymer plate preparation technical field.The application includes the following steps: under 60-80 ℃, polystyrene, synergist, smoke suppressant are mixed and pre-blended, then melt-blended under 180-200 ℃, modified masterbatch is obtained after granulation;Modified masterbatch, accelerate foaming agent are mixed and then put into mould, pentane gas is input to pressure 0.4-0.5MPa, after standing 4-5min, maintain pressure and carry out 1-2min microwave heating, then the mould is put into 13-15 ℃ water, after cooling, demoulding, obtain the foam board of rapid prototyping.The microwave heating treatment of the application effectively improves the forming speed of foam board;The introduction of synergist, smoke suppressant, accelerate foaming agent and other components further improves its forming speed, flame-retardant capacity and inhibition capacity.Therefore, the application has more extensive application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer board preparation technology, specifically to a rapid prototyping foam board and its processing technology. Background Technology

[0002] Foam board is a widely used lightweight porous material, with common types including polystyrene foam board, polyurethane foam board, and polyethylene foam board. Polystyrene foam board, in particular, is lightweight, has good sound and heat insulation properties, is easy to process, has low water absorption, and good electrical insulation properties. Therefore, it is widely used in building exterior wall insulation, packaging materials, sound insulation, and shock absorption. However, the molding process of polystyrene foam boards relies on a long foaming reaction time, mold cooling time, and curing process. For example, in compression molding, the diffusion of the foaming agent, the expansion of bubbles, and the shaping of the board typically take tens of minutes to several hours, making it difficult to meet the demands of large-scale, high-frequency production. Furthermore, the lengthy heating, pressurizing, and cooling processes consume a large amount of energy, and the low mold turnover rate results in high equipment idle costs. In addition, the slow cycle leads to increased labor and space costs, squeezing profit margins for businesses.

[0003] Meanwhile, polystyrene foam boards prepared by existing methods also have problems such as poor flame retardancy and large smoke release during combustion. Summary of the Invention

[0004] The purpose of this invention is to provide a rapid prototyping foam board and its processing technology, solving the following technical problems: Existing polystyrene foam boards still suffer from problems such as slow molding, poor flame retardancy, and large smoke release during combustion.

[0005] The objective of this invention can be achieved through the following technical solutions: A rapid-forming foam board comprises the following raw materials in parts by weight: 85-90 parts polystyrene, 7-10 parts synergist, 3-5 parts smoke suppressant, and 9-10 parts accelerated foaming agent.

[0006] Preferably, the synergist is prepared by the following method: Step A1: Add ammonium polyphosphate to deionized water and stir at 58-62℃ for 20-30 min. Then add silane coupling agent KH-550 and react for 2-3 h. After filtration, washing and vacuum drying, pretreated ammonium polyphosphate is obtained. Step A2: Dissolve nicotinamide in ethanol to obtain a nicotinamide solution; Step A3: Add ethanol and deionized water to ferric nitrate nonahydrate, stir for 20-30 min, then add pretreated ammonium polyphosphate and stir for 4-6 h. Then add nicotinamide solution and react at 78-82℃ for 19-21 h. After washing, drying, grinding and sieving, modified ammonium polyphosphate is obtained. Step A4: Mix modified ammonium polyphosphate and melamine cyanurate, add deionized water and sonicate for 30-35 minutes, then heat to 70-80℃ and stir for 2-2.2 hours, then spray dry, and finally heat treat at 118-122℃ for 1-1.2 hours and sieve to obtain the synergist.

[0007] Preferably, the ratio of deionized water, ammonium polyphosphate, and silane coupling agent KH-550 in step A1 is 20-24 mL: 7-8 g: 0.09-0.22 g; The ratio of nicotinamide to ethanol used in step A2 is 0.28-0.43g: 9-14mL.

[0008] Preferably, the ratio of ferric nitrate nonahydrate, ethanol, deionized water, pretreated ammonium polyphosphate, and nicotinamide solution in step A3 is 0.81-0.94g: 60-90mL: 1.5-2.3mL: 6-7g: 9-14mL; The sieve used for sieving in step A3 is 200 mesh; The ratio of modified ammonium polyphosphate, melamine cyanurate, and deionized water in step A4 is 6-7g: 3-4g: 21-44mL; The frequency of ultrasound in step A4 is 38-40kHz, and the power is 280-300W; The inlet temperature of the spray dryer described in step A4 is 180-200℃, and the outlet temperature is 80-90℃. The particle size distribution of the synergist after sieving in step A4 is 10-50 μm.

[0009] Preferably, the smoke suppressant is prepared as follows: Zinc molybdate and stearic acid are mixed and ball-milled with zirconia balls for 3.5-4 hours, and then filtered to obtain a smoke suppressant.

[0010] Preferably, the mass ratio of zinc molybdate, stearic acid, and zirconium oxide spheres is 11.3:0.11-0.22:60; The pore size of the filter membrane used in the filtration process is 100 nm.

[0011] Preferably, the preparation method of the foaming accelerator is as follows: Step B1: Dissolve the silane coupling agent KH-570 in anhydrous ethanol to obtain a KH-570 solution; Step B2: Mix talc powder with anhydrous ethanol and ball mill with zirconia balls for 6-8 hours. Then add KH-570 solution and stir at 58-62℃ for 2-2.2 hours. Finally, spray dry to obtain modified talc powder. Step B3: At 15-25℃, mix modified talc, azodicarbonamide, and zinc stearate for 25-30 minutes, sieve, and then spray onto an aqueous solution of ethylene-vinyl acetate copolymer to obtain an accelerated foaming agent.

[0012] Preferably, the ratio of silane coupling agent KH-570 to anhydrous ethanol in step B1 is 0.2-0.5g: 4-10mL; The ratio of talc powder, anhydrous ethanol, zirconium oxide balls, and KH-570 solution used in step B2 is 10-15g: 270-400g: 80-120g: 3-7.5mL; The inlet temperature for fog drying in step B2 is 180-200℃, and the outlet temperature is 80-90℃. The ratio of the modified talc, azodicarbonamide, zinc stearate, and ethylene-vinyl acetate copolymer aqueous solution used in step B3 is 10-15g: 5-8.5g: 0.1-0.24g: 4-6mL; The mass fraction of the ethylene-vinyl acetate copolymer aqueous solution in step B3 is 5%; The sieve used for sieving in step B3 is 200 mesh.

[0013] A rapid prototyping process for foam boards includes the following steps: Step S1: At 60-80℃, polystyrene, synergist and smoke suppressant are mixed and pre-blended for 10-15 min, then melt-blended at 180-200℃ for 20-25 min, and granulated to obtain modified masterbatch; Step S2: Mix the modified masterbatch and the accelerated foaming agent and put them into the mold. Purge pentane gas to a pressure of 0.4-0.5 MPa. Let it stand for 4-5 minutes, then maintain the pressure at 0.4-0.5 MPa and microwave heat for 1-2 minutes. Then put the mold into water at 13-15℃. After cooling to 40-50℃, demold to obtain a rapidly formed foam board.

[0014] Preferably, the rotation speed during pre-mixing in step S1 is 1000-1200 r / min; The rotation speed during melt blending in step S1 is 200-300 r / min; The microwave heating in step S2 has a frequency of 2450-2500MHz, a power of 10-15kW, a heating rate of 11-12℃ / s, and a heating temperature of 110-120℃.

[0015] As a further aspect of the present invention.

[0016] The beneficial effects of this invention are: This invention provides a rapid-forming foam board and its processing technology. The invention effectively improves the forming speed and flame retardancy of polystyrene foam board through the following methods, while also significantly reducing the amount of smoke released when polystyrene foam board is burned.

[0017] (1) The phosphoric acid produced by the decomposition of ammonium polyphosphate in the synergist of this invention promotes the dehydration and char formation of melamine cyanurate. At the same time, the released gas causes the char layer to expand, forming a porous heat insulation layer, which inhibits the thermal decomposition of the polymer matrix and the release of flammable gases. The iron and ferrous ions in the synergist can accelerate the dehydration and carbonization reaction of the polymer, reduce the char formation temperature, and improve the strength and density of the char layer, thereby enhancing the flame retardant efficiency. The amide group of nicotinamide in the synergist can form a stable complex with iron ions, inhibiting the oxidative degradation of polystyrene at high temperatures and increasing the thermal decomposition temperature of the material. The char layer formed by nicotinamide at high temperatures can effectively block the transfer of heat to the polymer matrix, delaying matrix degradation and allowing the foam board to maintain structural integrity for longer under high-temperature conditions. Nicotinamide and melamine cyanurate form a network structure through hydrogen bonds / amide bonds, making the char layer more stable at high temperatures and providing a longer-lasting barrier effect. At low temperatures, nicotinamide first releases ammonia to dilute oxygen, while at high temperatures, melamine cyanurate releases nitrogen and other gases to maintain the expansion of the char layer. The gradient gas production formed by the two can effectively maintain the flame retardant ability. The ammonia released by the decomposition of melamine cyanurate and nicotinamide can also react with the phosphoric acid from the decomposition of ammonium polyphosphate to form ammonium phosphate, which forms a "nano-water reservoir" in the char layer, blocking the release of combustion gases and smoke particles to the outside, inhibiting char layer rupture, and thus reducing smoke density. The ammonium polyphosphate and iron oxide in the synergist can also act as physical nucleating agents to promote the formation of uniform cells in the pentane foaming agent during microwave foaming, thereby improving the foaming ratio and cell density of the foam board.

[0018] (2) The smoke suppressant of the present invention promotes the dehydration and carbonization of the polymer matrix during the combustion of foam board, forming a dense carbon layer, which inhibits the release of combustible gases and the generation of smoke; the oxides produced by its decomposition can capture free radicals in combustion, slow down the combustion chain reaction, thereby reducing the generation of smoke precursors.

[0019] Stearic acid is adsorbed onto the surface of zinc molybdate particles through ball milling, reducing particle agglomeration tendency and improving its dispersibility in polystyrene. This physical barrier maximizes the inhibition of heat transfer and smoke diffusion, thereby enhancing smoke suppression efficiency. Simultaneously, it reduces filler-matrix interface defects, further improving mechanical properties. Zinc molybdate forms a synergistic "phosphorus-nitrogen-metal" effect with the synergist, promoting char layer formation, releasing inert gases to dilute oxygen, and stabilizing the char layer together with the synergist, inhibiting its breakage, thus reducing smoke release through the char layer.

[0020] (3) In the foaming accelerator of this invention, azodicarbonamide decomposes to produce gases such as nitrogen and carbon monoxide during subsequent microwave heating, accelerating gas generation, shortening foaming time, improving production efficiency, and promoting the expansion of polystyrene matrix to form a foam structure. The talc modified with silane coupling agent in the foaming accelerator can inhibit excessive expansion or merging of cells through physical inhibition, forming a more uniform microporous structure, improving the closed-cell rate and thermal insulation performance of the foam; talc particles can also act as foaming nucleation points, increasing the number of cells and reducing foam density. The aqueous solution of ethylene-vinyl acetate copolymer in the foaming accelerator forms a flexible polymer network after spray drying, which wraps the foaming agent and filler particles, improves the uniformity of component dispersion, prevents filler agglomeration or excessively high local concentration of foaming agent, and avoids defects such as "uneven density" or "brittleness" in the foam; the elastic segments of ethylene-vinyl acetate copolymer can also alleviate stress concentration when the foam is subjected to external force, reducing the risk of cracking. The metallic soap structure of zinc stearate in the foaming agent can moderately delay the decomposition temperature of azodicarbonamide, so that the foaming process matches the microwave heating rate and avoids "collapse" and "gas escape" caused by premature gas release.

[0021] The accelerator, modified masterbatch, and pentane gas also have a synergistic effect during the microwave foaming process, which can achieve rapid and uniform foaming, ensure consistent density in the thickness direction of the foam board, and reduce microwave heating time and pressure maintenance costs.

[0022] (4) The microwave heating of this invention features rapid heating and simultaneous internal and external heating, which allows the azodicarbonamide in the foaming agent to decompose uniformly in a short time, releasing gases such as nitrogen and forming dense cell nuclei. Rapid heating combined with a high-pressure environment can suppress premature gas escape, promoting uniform expansion of the cells in the polymer molten state, forming closed-cell foam with narrow particle size distribution and uniform structure. The short microwave heating time combined with pressure maintenance effectively inhibits the oxidative degradation of polystyrene at high temperatures, maintains the integrity of the molecular chain, and avoids the generation of small molecule volatiles such as styrene monomer, thereby improving the mechanical strength and heat resistance of the foam. Furthermore, microwave heating significantly shortens the foaming time, improves production efficiency, and reduces energy consumption.

[0023] Therefore, the polystyrene foam board prepared by this invention has excellent molding speed, flame retardancy, and extremely low smoke emission, as well as broad application prospects. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Unless otherwise specified, the following information pertains to some of the raw materials used in the following embodiments and comparative examples of this invention: Ammonium polyphosphate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S67475-500g; nicotinamide was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S13015-500g; ferric nitrate nonahydrate was purchased from Shanghai Xianding Biotechnology Co., Ltd., item number: FK477; melamine cyanurate was purchased from Shanghai Jieshikai Biotechnology Co., Ltd., item number: KA688966-25g; zinc molybdate was purchased from Hubei Jusheng Technology Co., Ltd., item number: JS4943; stearic acid was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: The following products were purchased: S30473-500g; Talc powder was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S30618-500g; Azodicarbonamide was purchased from Shanghai Mairui Biochemical Technology Co., Ltd., item number: M37780; Zinc stearate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S24319-500g; Ethylene-vinyl acetate copolymer was purchased from Henan Weitixi Chemical Technology Co., Ltd., item number: A0937788; Polystyrene was purchased from Shanghai Qincheng Biotechnology Co., Ltd., CAS: 9003-53-6.

[0026] Example 1: The processing technology for a rapid prototyping foam board is as follows: S1: Add 7g of ammonium polyphosphate to 20mL of deionized water and stir at 500r / min for 20min at 58℃. Then add 0.09g of silane coupling agent KH-550 and react for 2h. After filtration, washing and vacuum drying at 78℃ for 10h, pretreated ammonium polyphosphate is obtained. S2: Dissolve 0.28g of nicotinamide in 9mL of ethanol to obtain a nicotinamide solution; S3: Add 60 mL of ethanol and 1.5 mL of deionized water to 0.81 g of ferric nitrate nonahydrate, stir for 20 min, then add 6 g of pretreated ammonium polyphosphate and stir for 4 h. Then add 9 mL of nicotinamide solution and heat at 78 °C for 19 h. Then wash three times with 98% ethanol aqueous solution, dry at 58 °C for 12 h, grind and pass through a 200 mesh sieve to obtain modified ammonium polyphosphate. S4: Mix 6g of modified ammonium polyphosphate with 3g of melamine cyanurate, add 21mL of deionized water, and sonicate at 38kHz and 280W for 30min. Then heat to 70℃ and stir at 1000r / min for 2h. Spray dry at 180℃ and 80℃, and finally heat treat at 118℃ for 1h and sieve to obtain an synergist with a particle size distribution of 10-50μm. S5: Mix 11.3g of zinc molybdate with 0.11g of stearic acid and then ball mill it with 60g of zirconia balls at 280r / min for 3.5h. After filtration through a filter membrane with a pore size of 100nm, a smoke suppressant is obtained. S6: Dissolve 0.2g of silane coupling agent KH-570 in 4mL of anhydrous ethanol to obtain KH-570 solution; S7: Mix 10g of talc powder with 270g of anhydrous ethanol and ball mill with 80g of zirconia balls at 380r / min for 6h. Then add 3mL of KH-570 solution and stir at 58℃ for 2h. Then spray dry at an inlet temperature of 180℃ and an outlet temperature of 80℃ to obtain modified talc powder. S8: At 15℃, 10g of modified talc powder, 5g of azodicarbonamide and 0.1g of zinc stearate are mixed at 20r / min for 25min, passed through a 200-mesh sieve and then sprayed onto 4mL of a 5% (w / w) aqueous solution of ethylene-vinyl acetate copolymer to obtain an accelerator foaming agent. S9: At 60℃, 85g of polystyrene, 7g of synergist and 3g of smoke suppressant are mixed and pre-blended at 1000r / min for 10min, and then melt-blended at 180℃ at 200r / min for 20min. After granulation, the modified masterbatch is obtained. S10: Add 90g of modified masterbatch and 9g of accelerated foaming agent to a microwave foaming mold, introduce pentane gas to a pressure of 0.4MPa, let stand for 4 minutes, maintain the pressure of 0.4MPa while heating to 110℃ at a heating rate of 11℃ / s and microwave heating at a frequency of 2450MHz and a power of 10kW for 1 minute, then put the mold into 13℃ water, wait for it to cool down to 40℃, and demold to obtain a rapidly formed foam board.

[0027] Example 2: The processing technology for a rapid prototyping foam board is as follows: S1: Add 7.5g of ammonium polyphosphate to 22mL of deionized water and stir at 650r / min for 25min at 60℃. Then add 0.1g of silane coupling agent KH-550 and react for 2.5h. After filtration, washing and vacuum drying at 79℃ for 11h, pretreated ammonium polyphosphate is obtained. S2: Dissolve 0.35g of nicotinamide in 11.5mL of ethanol to obtain a nicotinamide solution; S3: Add 75 mL of ethanol and 1.9 mL of deionized water to 0.88 g of ferric nitrate nonahydrate, stir for 25 min, then add 6.5 g of pretreated ammonium polyphosphate and stir for 5 h. Then add 11.5 mL of nicotinamide solution and heat at 80 °C for 20 h. Then wash 4 times with 98% ethanol aqueous solution, dry at 59 °C for 13 h, grind and pass through a 200 mesh sieve to obtain modified ammonium polyphosphate. S4: Mix 6.5g of modified ammonium polyphosphate and 3.5g of melamine cyanurate, add 33mL of deionized water and sonicate at 39kHz and 290W for 33min. Then heat to 75℃ and stir at 1100r / min for 2.1h. Then spray dry at 190℃ and 85℃. Finally, heat treat at 120℃ for 1.1h and sieve to obtain an synergist with a particle size distribution of 10-50μm. S5: 11.3g zinc molybdate and 0.17g stearic acid were mixed and then ball-milled with 60g zirconia balls at 290r / min for 3.8h. The mixture was then filtered through a filter membrane with a pore size of 100nm to obtain a smoke suppressant. S6: Dissolve 0.4g of silane coupling agent KH-570 in 8mL of anhydrous ethanol to obtain KH-570 solution; S7: Mix 12.5g of talc powder with 335g of anhydrous ethanol and ball mill with 100g of zirconia balls at 390r / min for 7h. Then add 5.5mL of KH-570 solution and stir at 60℃ for 2.1h. Finally, spray dry at an inlet temperature of 190℃ and an outlet temperature of 85℃ to obtain modified talc powder. S8: At 20℃, 12.5g of modified talc powder, 7g of azodicarbonamide and 0.18g of zinc stearate are mixed at 25r / min for 28min, passed through a 200-mesh sieve and then sprayed onto 5mL of a 5% (w / w) aqueous solution of ethylene-vinyl acetate copolymer to obtain an accelerator foaming agent. S9: At 70℃, 88g of polystyrene, 8g of synergist and 4g of smoke suppressant are mixed and pre-blended at 1100r / min for 13min, and then melt-blended at 190℃ at 250r / min for 23min. After granulation, the modified masterbatch is obtained. S10: Add 95g of modified masterbatch and 9.5g of accelerated foaming agent to a microwave foaming mold, introduce pentane gas to a pressure of 0.45MPa, let stand for 4.5min, maintain the pressure of 0.45MPa while heating at a rate of 11.5℃ / s to 115℃ and microwave heating at a frequency of 2480MHz and a power of 13kW for 1.5min, then put the mold into 14℃ water, wait for it to cool down to 45℃, and demold to obtain a rapidly formed foam board.

[0028] Example 3: The processing technology for a rapid prototyping foam board is as follows: S1: Add 8g of ammonium polyphosphate to 24mL of deionized water and stir at 800r / min for 30min at 62℃. Then add 0.22g of silane coupling agent KH-550 and react for 3h. After filtration, washing and vacuum drying at 80℃ for 12h, pretreated ammonium polyphosphate is obtained. S2: Dissolve 0.43g of nicotinamide in 14mL of ethanol to obtain a nicotinamide solution; S3: Add 90 mL of ethanol and 2.3 mL of deionized water to 0.94 g of ferric nitrate nonahydrate, stir for 30 min, then add 7 g of pretreated ammonium polyphosphate and stir for 6 h. Then add 14 mL of nicotinamide solution and heat at 82 °C for 21 h. Then wash 5 times with 98% ethanol aqueous solution, dry at 60 °C for 15 h, grind and pass through a 200 mesh sieve to obtain modified ammonium polyphosphate. S4: Mix 7g of modified ammonium polyphosphate with 4g of melamine cyanurate, add 44mL of deionized water, and sonicate at 40kHz and 300W for 35min. Then heat to 80℃ and stir at 1200r / min for 2.2h. Then spray dry at 200℃ inlet and 90℃ outlet. Finally, heat treat at 122℃ for 1.2h and sieve to obtain an synergist with a particle size distribution of 10-50μm. S5: 11.3g zinc molybdate and 0.22g stearic acid were mixed and ball-milled with 60g zirconia balls at 300r / min for 4h. The mixture was then filtered through a filter membrane with a pore size of 100nm to obtain a smoke suppressant. S6: Dissolve 0.5g of silane coupling agent KH-570 in 10mL of anhydrous ethanol to obtain KH-570 solution; S7: Mix 15g of talc powder with 400g of anhydrous ethanol and ball mill with 120g of zirconia balls at 400r / min for 8h. Then add 7.5mL of KH-570 solution and stir at 62℃ for 2.2h. Then spray dry at an inlet temperature of 200℃ and an outlet temperature of 90℃ to obtain modified talc powder. S8: At 25℃, 15g of modified talc powder, 8.5g of azodicarbonamide and 0.24g of zinc stearate are mixed at 30r / min for 30min, passed through a 200-mesh sieve and then sprayed onto 6mL of a 5% (w / w) aqueous solution of ethylene-vinyl acetate copolymer to obtain an accelerator foaming agent. S9: At 80℃, 90g of polystyrene, 10g of synergist and 5g of smoke suppressant are mixed and pre-blended at 1200r / min for 15min, and then melt-blended at 200℃ at 300r / min for 25min. After granulation, the modified masterbatch is obtained. S10: Add 100g of modified masterbatch and 10g of accelerated foaming agent to a microwave foaming mold, introduce pentane gas to a pressure of 0.5MPa, let stand for 5 minutes, maintain the pressure at 0.5MPa while heating at a rate of 12℃ / s to 120℃ and perform microwave heating at a frequency of 2500MHz and a power of 15kW for 2 minutes. Then place the mold in 15℃ water, wait for it to cool down to 50℃, and demold to obtain a rapidly formed foam board.

[0029] Comparative Example 1: Compared with Example 1, this comparative example only replaces "6g of pretreated ammonium polyphosphate" added during the preparation of modified ammonium polyphosphate in S3 with "6g of ammonium polyphosphate". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapidly formed foam board is obtained.

[0030] Comparative Example 2: Compared with Example 1, this comparative example only replaces the "6g modified ammonium polyphosphate" added in the preparation process of the synergist in S4 with the "6g pretreated ammonium polyphosphate" prepared in S2. All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapidly formed foam board is obtained.

[0031] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "7g synergist" added in the modified masterbatch process of S9 with the "7g modified ammonium polyphosphate" prepared in S3. All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapidly formed foam board is obtained.

[0032] Comparative Example 4: Compared with Example 1, this comparative example only omits the addition of "0.11g stearic acid" in the preparation of the smoke suppressant in S5. All other steps and parameters are the same, and will not be repeated here. The final product is a rapidly formed foam board.

[0033] Comparative Example 5: Compared with Example 1, this comparative example only replaces "10g modified talc" added during the preparation of the accelerated foaming agent in S8 with "10g talc". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapidly formed foam board is obtained.

[0034] Comparative Example 6: Compared with Example 1, this comparative example only omits the addition of "5g azodicarbonamide" in the preparation of the accelerated foaming agent in S8. All other steps and parameters are the same, and will not be repeated here. The final product is a rapidly formed foam board.

[0035] Comparative Example 7: Compared with Example 1, this comparative example only omits the addition of "3g smoke suppressant" during the preparation of the modified masterbatch in S9. All other steps and parameters are the same, and will not be repeated here. The final product is a rapidly formed foam board.

[0036] Comparative Example 8: Compared with Example 1, this comparative example only replaces the "9g accelerator foaming agent" added in the rapid prototyping foam board preparation process of S10 with "9g modified talc powder". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapid prototyping foam board is obtained.

[0037] Comparative Example 9: Compared with Example 1, this comparative example only replaces the step of "maintaining a pressure of 0.4 MPa and performing microwave heating at a frequency of 2450 MHz, a power of 10 kW, a heating rate of 11 °C / s, and a heating temperature of 110 °C for 1 minute after standing for 4 minutes" in the rapid prototyping foam board preparation process of S10 with "maintaining a pressure of 0.4 MPa after standing for 4 minutes, and simultaneously heating to 110 °C at a heating rate of 11 °C / s and heating for 1 minute". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a rapid prototyping foam board is obtained.

[0038] Performance testing: Determination of maximum smoke density (SDR): Referring to ASTM E662, "Test Method for Smoke Production and Smoke Density of Solid Materials," the maximum smoke density of a foam board with dimensions of 150 mm in length, 100 mm in width, and 4 mm in thickness was determined over 20 minutes under both flame-lit and flameless conditions using the smoke density box method (NBS smoke box). The maximum smoke density of the rapidly prototyping foam boards prepared in Examples 1-3 and Comparative Examples 1-9 was tested using this method, and the test results are shown in Table 1.

[0039] Determination of combustion performance: Referring to GB / T 2406.2-2012 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test", foam boards were cut into pieces 150 mm long, 10 mm wide, and 4 mm thick, and conditioned at 25°C and 50% relative humidity for 50 h. The oxygen index (%) was then measured. The oxygen index (%) of the rapidly prototyping foam boards prepared in Examples 1-3 and Comparative Examples 1-9 were tested using this method, and the results are shown in Table 1.

[0040] Referring to GB / T 2408-2021 "Determination of Burning Performance of Plastics - Horizontal and Vertical Methods", foam boards were cut into pieces 127mm long, 12.7mm wide, and 3.0mm thick. The pieces were vertically fixed with their lower ends 10mm from the methane flame of the burner. The sample was ignited for 10 seconds, then the flame was removed, and the following times were recorded: first burning time (t1, flame extinguishing time); if dripping occurred, it was observed whether it ignited the absorbent cotton; the sample was then ignited again for 10 seconds, and the second burning time (t2) was recorded. The flame retardancy rating of the foam board was then determined according to this grading standard (V-0: t1≤10s, t2≤30s, no dripping ignition; V-1: t1≤30s, t2≤60s, no dripping ignition; V-2: dripping ignition of absorbent cotton is allowed, the rest is the same as V-1). The flame retardancy (grade) of the rapidly prototyping foam boards prepared in Examples 1-3 and Comparative Examples 1-9 were tested according to this method, and the test results are shown in Table 1.

[0041] Determination of dimensional stability: Referring to the test standard GB / T 8811-2008 "Test Method for Dimensional Stability of Rigid Foamed Plastics", foam boards were cut into lengths of 100 mm, widths of 100 mm, and thicknesses of 50 mm and conditioned in an environment of 25°C and 50% relative humidity for 10 hours. The dimensions before and after treatment at 70°C for 24 hours were then measured, and the corresponding dimensional stability (%) was calculated. The dimensional stability (%) of the rapidly prototyping foam boards prepared in Examples 1-3 and Comparative Examples 1-9 was tested using this method, and the test results are shown in Table 1.

[0042] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-9:

[0043] Data Analysis: As can be seen from Table 1, the rapid prototyping foam board prepared by the embodiments of the present invention can be rapidly formed while also having excellent smoke suppression, flame retardancy and dimensional stability.

[0044] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A rapid-molding foam board, characterized in that, The raw materials include the following parts by weight: 85-90 parts polystyrene, 7-10 parts synergist, 3-5 parts smoke suppressant, and 9-10 parts foaming accelerator.

2. The rapid prototyping foam board according to claim 1, characterized in that, The preparation method of the synergist is as follows: Step A1: Add ammonium polyphosphate to deionized water and stir at 58-62℃ for 20-30 min. Then add silane coupling agent KH-550 and react for 2-3 h. After filtration, washing and vacuum drying, pretreated ammonium polyphosphate is obtained. Step A2: Dissolve nicotinamide in ethanol to obtain a nicotinamide solution; Step A3: Add ethanol and deionized water to ferric nitrate nonahydrate, stir for 20-30 min, then add pretreated ammonium polyphosphate and stir for 4-6 h. Then add nicotinamide solution and react at 78-82℃ for 19-21 h. After washing, drying, grinding and sieving, modified ammonium polyphosphate is obtained. Step A4: Mix modified ammonium polyphosphate and melamine cyanurate, add deionized water and sonicate for 30-35 minutes, then heat to 70-80℃ and stir for 2-2.2 hours, then spray dry, and finally heat treat at 118-122℃ for 1-1.2 hours and sieve to obtain the synergist.

3. The rapid prototyping foam board according to claim 2, characterized in that, The ratio of deionized water, ammonium polyphosphate, and silane coupling agent KH-550 used in step A1 is 20-24 mL: 7-8 g: 0.09-0.22 g; The ratio of nicotinamide to ethanol used in step A2 is 0.28-0.43g: 9-14mL.

4. The rapid prototyping foam board according to claim 2, characterized in that, The ratio of ferric nitrate nonahydrate, ethanol, deionized water, pretreated ammonium polyphosphate, and nicotinamide solution used in step A3 is 0.81-0.94g: 60-90mL: 1.5-2.3mL: 6-7g: 9-14mL; The ratio of modified ammonium polyphosphate, melamine cyanurate, and deionized water in step A4 is 6-7g: 3-4g: 21-44mL; The inlet temperature of the spray drying process described in step A4 is 180-200℃, and the outlet temperature is 80-90℃.

5. The rapid prototyping foam board according to claim 1, characterized in that, The preparation method of the smoke suppressant is as follows: Zinc molybdate and stearic acid are mixed and ball-milled with zirconia balls for 3.5-4 hours, and then filtered to obtain a smoke suppressant.

6. The rapid prototyping foam board according to claim 5, characterized in that, The mass ratio of zinc molybdate, stearic acid, and zirconium oxide spheres is 11.3:0.11-0.22:

60.

7. The rapid prototyping foam board according to claim 1, characterized in that, The preparation method of the foaming accelerator is as follows: Step B1: Dissolve the silane coupling agent KH-570 in anhydrous ethanol to obtain a KH-570 solution; Step B2: Mix talc powder with anhydrous ethanol and ball mill with zirconia balls for 6-8 hours. Then add KH-570 solution and stir at 58-62℃ for 2-2.2 hours. Finally, spray dry to obtain modified talc powder. Step B3: At 15-25℃, mix modified talc, azodicarbonamide, and zinc stearate for 25-30 minutes, sieve, and then spray the mixture onto an aqueous solution of ethylene-vinyl acetate copolymer to obtain an accelerated foaming agent.

8. The rapid prototyping foam board according to claim 7, characterized in that, The ratio of silane coupling agent KH-570 to anhydrous ethanol in step B1 is 0.2-0.5g: 4-10mL; The ratio of talc powder, anhydrous ethanol, zirconium oxide balls, and KH-570 solution used in step B2 is 10-15g: 270-400g: 80-120g: 3-7.5mL; The inlet temperature for fog drying in step B2 is 180-200℃, and the outlet temperature is 80-90℃. The ratio of the modified talc, azodicarbonamide, zinc stearate, and ethylene-vinyl acetate copolymer aqueous solution used in step B3 is 10-15g: 5-8.5g: 0.1-0.24g: 4-6mL; The mass fraction of the ethylene-vinyl acetate copolymer aqueous solution in step B3 is 5%.

9. A processing technology for rapid prototyping foam boards, characterized in that, Includes the following steps: Step S1: At 60-80℃, polystyrene, synergist and smoke suppressant are mixed and pre-blended for 10-15 min, then melt-blended at 180-200℃ for 20-25 min, and granulated to obtain modified masterbatch; Step S2: Mix the modified masterbatch and the accelerated foaming agent and put them into the mold. Purge pentane gas to a pressure of 0.4-0.5 MPa. Let it stand for 4-5 minutes, then maintain the pressure at 0.4-0.5 MPa and microwave heat for 1-2 minutes. Then put the mold into water at 13-15℃. After cooling to 40-50℃, demold to obtain a rapidly formed foam board.

10. The processing technology for rapid prototyping foam boards according to claim 9, characterized in that, The microwave heating in step S2 has a frequency of 2450-2500MHz, a power of 10-15kW, a heating rate of 11-12℃ / s, and a heating temperature of 110-120℃.